2019
DOI: 10.1016/j.isci.2019.07.040
|View full text |Cite
|
Sign up to set email alerts
|

Coxsackievirus B Persistence Modifies the Proteome and the Secretome of Pancreatic Ductal Cells

Abstract: Summary The group B Coxsackieviruses (CVB), belonging to the Enterovirus genus, can establish persistent infections in human cells. These persistent infections have been linked to chronic diseases including type 1 diabetes. Still, the outcomes of persistent CVB infections in human pancreas are largely unknown. We established persistent CVB infections in a human pancreatic ductal-like cell line PANC-1 using two distinct CVB1 strains and profiled infection-induced changes in cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 97 publications
(185 reference statements)
6
33
0
Order By: Relevance
“…In this way, IAV alkalinizes the lumen of the Golgi complex and the trans-Golgi network ( TGN ), preventing premature conformational changes in the viral hemagglutinin during exit of viral progeny [ 80 ] while directing trafficking of the hemagglutinin along the secretory pathway to the PM [ 81 ]. The CVB viroporin releases charged calcium ions and protons from the Golgi complex and ER into the cytosol [ 82 ], reducing cellular protein trafficking and promoting persistent CVB infection [ 82 , 83 ]. This process additionally inhibits glycosylation of proteins in the Golgi complex, resulting in dampened host cell immune responses [ 84 ].…”
Section: Egressmentioning
confidence: 99%
“…In this way, IAV alkalinizes the lumen of the Golgi complex and the trans-Golgi network ( TGN ), preventing premature conformational changes in the viral hemagglutinin during exit of viral progeny [ 80 ] while directing trafficking of the hemagglutinin along the secretory pathway to the PM [ 81 ]. The CVB viroporin releases charged calcium ions and protons from the Golgi complex and ER into the cytosol [ 82 ], reducing cellular protein trafficking and promoting persistent CVB infection [ 82 , 83 ]. This process additionally inhibits glycosylation of proteins in the Golgi complex, resulting in dampened host cell immune responses [ 84 ].…”
Section: Egressmentioning
confidence: 99%
“…These truncated viral populations displayed 5 NCR deletions in RNA domain-I disrupting secondary RNA structures, which could impair viral RNA sensing by RLRs and result in a modulation of type I IFN expression in target cells [17]. Given that 5 TD viruses are low replicating forms, the generation or maintenance of such variants could be an efficient process for EV-B to develop a chronic persistent infection in human target cells long after the acute infection phase [16,18,[144][145][146][147]. The combination of low-level replication and translation activities of naturally produced 5 TD viruses, associated with the capacity of these RNA forms to modulate type-I IFN response activation pathway could explain long-lasting detection of EV-B genome in some human target tissues such as heart and pancreas.…”
Section: Involvement Of Natural 5 Terminally Deleted Ev-b Rna Forms Imentioning
confidence: 99%
“…The gut virome is known to be associated with the initiation of T1D, in which many in vitro and in vivo studies identified a positive correlation between the acute viral infection and the development of T1D [ 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 ]. T1D-associated viruses include enteroviruses such as coxsackievirus B4 ( CV-B4 ) which is known to mediate a low-grade pancreatic inflammation by enhancing viral replication, affecting the expression of β cell differentiation proteins, and lowering the expression of mitochondrial antiviral signaling proteins leading to persistent infection [ 130 ]. CV-B4 is also known to lower the expression of HLA class I molecules at the surface of the infected pancreatic beta cells which are then targeted by the activated NK cells leading to cytolysis [ 120 , 130 , 131 ].…”
Section: Gut Microbiome Immunity and T1dmentioning
confidence: 99%
“…T1D-associated viruses include enteroviruses such as coxsackievirus B4 ( CV-B4 ) which is known to mediate a low-grade pancreatic inflammation by enhancing viral replication, affecting the expression of β cell differentiation proteins, and lowering the expression of mitochondrial antiviral signaling proteins leading to persistent infection [ 130 ]. CV-B4 is also known to lower the expression of HLA class I molecules at the surface of the infected pancreatic beta cells which are then targeted by the activated NK cells leading to cytolysis [ 120 , 130 , 131 ]. A recent report from the TEDDY study indicated that young children with a genetic risk for T1D experienced a prolonged enteroviruses type B and adenovirus infections that precede the development of T1D [ 120 , 121 , 130 , 132 , 133 , 134 ].…”
Section: Gut Microbiome Immunity and T1dmentioning
confidence: 99%